In vivo and in vitro Characterization of a Partial Mu Opioid Receptor Agonist, NKTR-181, Supports Future Therapeutic Development - Lee, Alex S.; Tiwari, Suchi; Bishop, Isabel; Matossian, Vartan; Romaneschi, Nicole; Miyazaki, Takahiro; VanderVeen, Laurie; Zalevsky, Jonathan; DeFea, Kathryn; Cahill, Catherine M.; Walwyn, Wendy M. (Frontiers in Pain Research, 2021)
Mu opioid receptor (MOPr) agonists are well-known and frequently used clinical analgesics but are also rewarding due to their highly addictive and often abusive properties. This may lead to opioid use disorder (OUD) a disorder that effects millions of people worldwide. Therefore, novel compounds are urgently needed to treat OUD. As opioids are effective analgesics and OUD often occurs in conjunction with chronic pain, these novel compounds may be opioids, but they must have a low abuse liability. This could be mediated by diminishing or slowing blood-brain barrier transport, slowing target receptor binding kinetics, and showing a long half-life. NKTR-181 is a PEGylated oxycodol and a MOPr agonist that has slowed blood-brain barrier transport, a long half-life, and diminished likeability in clinical trials. In this study, we examined the signaling and behavioral profile of NKTR-181 in comparison with oxycodone to determine whether further therapeutic development of this compound may be warranted. For this preclinical study, we used a number of in vitro and in vivo assays. The signaling profile of NKTR-181 was determined by the electrophysiological assessment of MOPr-Ca2+ channel inhibition in the nociceptive neurons of rodent dorsal root ganglia. Heterologous cell-based assays were used to assess biased agonism and receptor trafficking. Different rodent behavioral models were used to define the NKTR-181-induced relief of effective and reflexive nociception and drug-seeking behavior as assessed by an intravenous self-administration (IVSA) of NKTR-181. We found that NKTR-181 and oxycodone are partial agonists in G-protein signaling and Ca2+ channel inhibition assays and promote limited MOPr desensitization. However, NKTR-181 inhibits Ca2+ channels by a different mechanism than oxycodone and induces a different pattern of arrestin recruitment. In addition, NKTR-181 has a slower receptor on-rate and a slower rate of Ca2+ channel coupling than oxycodone. This signaling profile is coupled with a slower onset of antinociception and limited drug-seeking behavior in comparison with oxycodone. Together with its known long half-life and slow blood-brain barrier transport, these data suggest that NKTR-181 could be further studied as a pharmacotherapeutic treatment modality for OUD.